PERKEMBANGAN USAHA SEPATU BUNUT SEBAGAI HOME INDUSTRY DI KECAMATAN KISARAN BARAT KABUPATEN ASAHAN - Cyntia Amelia Siregar (EKSYA : Jurnal Ekonomi Syariah, 2022)
One of the symbols of the Asahan Regency Range which is a typical souvenir of Asahan Regency is a bunut shoe. The word "Bunut" comes from the name of the village where the main production of these leather shoes is. The rubber plantation in Bunut village is run by PT. Uniroyal, famous in 1970. Therefore, this area cultivates the raw resources of rubber plantations, which are famous as the location for making leather shoes with the name "Bunut shoes", belonging to Cole Haan, an American citizen. To prevent individuals from wearing boots arbitrarily, the finished product is exported to America for sale and can only be used domestically by manufacturing employees who have certificates of ownership. The purpose of this study is to determine the changes that have occurred in the shoe industry throughout its history. The library technique was used by the author to compose this essay. Bunut shoes are a new style for the community that is allowed to be worn by all circles of society without any additional distinction between groups. Until now, the emergence of Bunut shoes can change the economic status of the craftsmen.